User Experience Evaluation of BPOM Mobile Application Using User Experience Questionnaire and Focus Group Discussion Method - Afifah Muthmainnah; Devi Ajeng Efrilianda (Universitas Negeri Semarang, 2024)
The Indonesian Food and Drug Authority (BPOM) as a government agency has developed the BPOM Mobile application to make it easier for the public to check the safety of drug and food products in circulation. From the research results, several user experience problems were found on BPOM Mobile, especially in the scan product feature. User experience evaluation needs to be carried out to measure the comfort felt by the user and determine the user's level of understanding of the application being used. This research aims to evaluate the user experience on BPOM Mobile using the User Experience Questionnaire and Focus Group Discussion methods. The sampling technique used was purposive sampling which was based on the criteria of public users who had used the scan product feature and were 18-25 years old and had a sample size based on the User Experience Questionnaire guidelines of 30 people. Respondents were 6 users who were willing to do a Focus Group Discussion exploring perceptions and problems in detail related to 6 aspects of the User Experience Questionnaire and aspects of visual aesthetics. The research results show that the BPOM Mobile application currently has a neutral user experience score on the attractiveness, perspicuity, efficiency, dependability, and novelty scales and a positive user experience score on the stimulation scale. Based on the Focus Group Discussion, 20 negative perceptions and problems were found, with details of 2 perceptions and problems of attractiveness, 3 perceptions and problems of perspicuity, 4 perceptions and problems of efficiency, 5 perceptions and problems of dependability, 1 perception and problem of novelty, and 5 perceptions and problems of visual aesthetics, while stimulation obtained 1 positive perception. The problems obtained were corrected through a prototype and resulted in positive user experience values in all aspects.